Using Art-Based Strategies in Group-Based Counselor Supervision. Issue 1 (2nd January 2017) - Liberati, Ryan; Agbisit, Melody
ABSTRACT: In addition to course work and experiential learning experiences, a vital aspect to counselor training is clinical supervision. Supervision acts as a mediator bridging the gap between theory and practice. Using creative interventions has been increasing in clinical work and may be beneficial to be used more in training counseling students. One way to incorporate creative and expressive techniques into a counseling program is to use art-based strategies in clinical group supervision. Research and clinical experiences are discussed.